Budget Participation dan Psychological Capital Pada Creative Attitude di Sekolah Muhammadiyah Unggul Jawa Timur - Junjunan, Mochammad Ilyas; Nawangsari, Ajeng Tita; Abdani, Fadlil (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to examine the level of budget participation and physicological capital toward the creative attitude in Sekolah Muhammadiyah Unggul Jawa Timur. We used 148 combined sample which consist of educators and education staff who participated in the 2018 budget preparation. The variables used in this study are participation and physicological capital which are measured by a person’s positive mental state including resilience, optimism, hope and self efficiacy. The study indicate that the budget participation in a supportive school environment will have a positive impact on the behavior of teachers and employeesin creating new innovate and supperior programs.